ISSUES OF INTERNATIONAL LEGAL REGULATION OF TOURISM ACTIVITY (Ta'limning zamonaviy transformatsiyasi, 2024)
In order to maintain the legal order in the field of international tourism, mutual cooperation of countries is carried out with specific international rules and agreements. It includes a generalized system of interstate agreements and conditions, visas, legal protection, certificates and other legal frameworks for the regulation of the tourism sector. There is no basic norm in the international legal regulation of the system. But the World Tourism Organization of the United Nations plays an important role in the development of the tourism industry and its regulation.